Ober die statistische Abschätzung der Entropie in den homogenen markoffschen Ketten - Misevičius, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. В. Мисевичюс. О статической оценке энтропии в однородной цепи МарковаE. Misevičius. Apie homogeninės Markovo grandinės entropijos statistikinį įvertinimą